Conservative management of a large brain abscess in a child with severe manifestations: A case report from Syria - Mouhammed Ali Keblawi; Amr Hamza; Abdualh Fattal; Ghina Ghannam; Ahmad Rami Rahmeh; Sami Rahmeh; Mouhammed Ali Serio (Clinical Case Reports, 2021)
Abstract Otogenic brain abscesses are rare but usually life‐threatening conditions particularly in developing countries. Our patient attended to the emergency department with extremely serious manifestations due to a large brain abscess. The borderline dimensions of the abscess (2.4 cm) with (GCS <12) as well as the lack of surgical capabilities were the factors that addressed to treat her with the available medication only. Fortunately, 2‐year follow‐up did not show any recurrence. This case sheds a light on unusual management of large abscesses in imperfect circumstances, which makes it high educational value.